2016
DOI: 10.1007/s10068-016-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic andantioxidant properties, and α-amylase and α-glucosidase inhibition effects of triterpene saponins from Piper auritum

Abstract: Bioactivity-guided fractionation of methanol extracts from leaves of produced four triterpenoid saponin compounds. Structures were established based on interpretation of mass spectrometry (MS), nuclear magnetic resonance (NMR) data. 21-(-methoxycinnamoyl)-olean-12-ene-28oic cid-3--α-L-arabinopyranosyl-(1→2)-β-D-glucopyranoside () and olean-12-ene-28 methyl ester-3--α-L-arabinofuranosyl-(1→2)-β-D-glucopyranoside () were orally administered to diabetic mice at dosage of 10 mg/kg of body weight per day for 30 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…In this study, the content of GSH was not significantly affected by saccharicterpenin. This result was different from a previous study, which stated that triterpenoid saponins (a component of saccharicterpenin) can significantly increase the content of GSH in the pancreas of rats ( Gutierrez, 2016 ). This conflict may be because of the difference in tissues.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, the content of GSH was not significantly affected by saccharicterpenin. This result was different from a previous study, which stated that triterpenoid saponins (a component of saccharicterpenin) can significantly increase the content of GSH in the pancreas of rats ( Gutierrez, 2016 ). This conflict may be because of the difference in tissues.…”
Section: Discussioncontrasting
confidence: 99%
“…Glutathione (GSH) is a major non-enzymatic antioxidant that can remove free radicals. The content of GSH was improved by triterpenoid saponins (a component of saccharicterpenin) in the liver of rats as reported by Gutierrez (2016) , who suggested that non-enzymatic antioxidants were increased by triterpenoid saponins. However, the effect of saccharicterpenin on non-enzymatic components is unknown.…”
Section: Introductionsupporting
confidence: 52%
“…Diabetes is a serious health problem growing at alarming rates around the world. It is reported to constitute the 16th leading cause of global mortality and caused various complications and disorders such as pain, hyperlipidemia, cardiovascular diseases and inflammation (Perez Gutierrez, 2016;Bahlil et al, 2020;Spínola et al, 2020). In this respect, Ephedra alata extracts many synthetic disaccharidase and lipase inhibitors have been reported to reduce plasma glucose and lipid levels via delaying glucose and lipid absorption and retarding the liberation of glucose from oligosaccharides and disaccharides from dietary complex carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…Infusion of P. auritum is traditionally used to accelerate childbirth, whereas Mayas apply fresh leaves to heal wounds [2] . Leaves are also used as emollient, diuretic, antirheumatic, abortifacient, and to treat dermatological illnesses [2–4] . The plant is frequently used as a spice because of its pleasant smell and particular flavor [3] .…”
Section: Introductionmentioning
confidence: 99%